Bias Gender Dalam Pengasuhan: Implikasinya Terhadap Regulasi Emosi Dan Kepercayaan Diri Anak Usia Dini - iftitahun nabilah; Shibi Zuharoul Mardliyah; Neila Meutyarachma (Pusat Studi Gender dan Anak (PSGA) Universitas Tarbiyatut Tholabah Lamongan, Jawa Timur Indoensia, 2026)
This study is motivated by the persistence of gender bias in early childhood parenting practices, which potentially affects children’s socio-emotional development. The aim of this study is to analyze the implications of gender bias in parenting on emotional regulation and self-confidence in early childhood. The method employed is a literature review. The findings indicate that gender bias in parenting manifests in differences in treatment, expectations, and stimulation between boys and girls. These conditions impact children’s emotional regulation, where restrictions on emotional expression may hinder adaptive emotional management, and also influence self-confidence through unequal opportunities for exploration and decision-making. The study concludes that gender bias in parenting simultaneously affects emotional regulation and self-confidence in early childhood. This research contributes to providing a comprehensive understanding of the importance of gender-responsive parenting in supporting optimal socio-emotional development in children.